Librarians at work - Kenney, Karen Latchana; Dumm, Brian Caleb (Edina, Minn. : Magic Wagon, 2010)
Learn about the important roles of the workers in your community. Do you know what tools, training, technology, and problems these important individuals face every day? Come meet your community workers!
Being a librarian -- Helping others -- At work -- Problems on the job -- Tools librarians need -- Technology at work -- Special skills and training -- In the community -- A day as a librarian.
Includes index.
"Looking glass library"--P. [4] of cover.
Keywords: Librarians -- Juvenile literature; Library science -- Vocational guidance -- Juvenile literature; Librarians; Library science -- Vocational guidance